Combining Mo–Cu/HZSM-5 with a two-stage catalytic pyrolysis system for pine sawdust thermal conversion. (15th June 2015) - Huang, Yinbin; Wei, Lin; Crandall, Zachery; Julson, James; Gu, Zhengrong
Abstract: Mo–Cu/HZSM-5 catalysts for pine sawdust thermal conversion were prepared using an impregnation method. The Mo–Cu/HZSM-5 catalysts and HZSM-5 were characterized by Brunauer–Emmett–Teller (BET), X-ray diffraction (XRD) and transmission electron microscopy (TEM). All characterization results indicated that the introduction of CuO is beneficial to the dispersion of MoO3 in the HZSM-5. Combined with the two-stage catalytic pyrolysis system, the Mo–Cu/HZSM-5 catalysts were used for pine sawdust thermal conversion. The products included gas, bio-oil and bio-char. The gas was analyzed by Gas chromatography (GC). Gas chromatography–mass spectrometry (GC–MS) was used to identify the compounds in bio-oils. The water content, higher heating value (HHV) and viscosity of bio-oils were measured. The HHV and elements of bio-char were determined. The results indicated that Mo(3%)–Cu(3%)/HZSM-5 treatment yielded the highest amount of C6 –C12 hydrocarbons, showed a robust ability to convert methane in the gas to bio-oil, and displayed no significant difference in the properties of bio-char when compared to different treatments in the same pyrolysis conditions.